El Mutakallimûn (masters of the word) - Maṭar, Aḥmad 1956- (Wrasse Records, 2015)
Die algerische Sängerin hat einige bekannte und wichtige Gedichte der arabischen Welt des vergangenen Jahrtausends vertont. Autoren: Ahmed Abou Tayeb "Al Mutanabi", Ilya Abou Madi, Ahmet Matar, Abou El Kacem El Chabbi, Zouhair Ibn Abi Salma, Qays Ibn Mullawah "Majnun Layla", Al Asmai
Program notes by Andy Morgan and song lyrics in English and French (32 unnumbered pages : color illustrations) inserted in container
Enth.: Bima El' Taaloul. Lastou Adri. Ayna. Hadari. Sa'imtou. El houriya. Faya Layla. El Khaylou wa el laylou. El boulbouli. Saàïche